A179 FEATURES OF THE METABOLIC SYNDROME ARE ASSOCIATED WITH LACK OF SERUM ALT NORMALIZATION DURING THERAPY FOR CHRONIC HEPATITIS B. (1st March 2018) - Fung, S; Khan, M; Yatsuhashi, H; Tak, W; Celen, M; Flaherty, J; Kim, K; Myers, R P
Abstract: Background: Despite complete suppression of HBV DNA with antiviral agents, serum alanine aminotransferase (ALT) levels fail to normalize in some patients with chronic hepatitis B (CHB). Aims: Our objective was to evaluate factors associated with persistent ALT elevation during treatment with tenofovir alafenamide (TAF) or tenofovir disoproxil fumarate(TDF). Methods: Adults with CHB enrolled in two Phase 3 studies of TAF 25 mg QD vs. TDF 300 mg QD (Study GS-US-320-0108 in HBeAg- and GS-US-320-0110 in HBeAg+ subjects) were included. Rates of ALT normalization at Weeks 12 and 48 were determined using reference ranges recommended by AASLD (≤19 U/L for women, ≤30 for men). A sensitivity analysis examined ALT normalization according to central laboratory (Covance) criteria (<69 yrs:≤34 U/L for women, ≤43 for men; ≥69 yrs: ≤32 U/L for women, ≤35 for men). Associations between host, viral and treatment-related factors, including virologic suppression (HBV DNA <29 IU/mL; Roche COBAS Taqman), with persistent ALT elevation at Week 48 were determined using logistic regression. Results: Based on AASLD criteria, 1, 276 of 1, 301 subjects (98%) had abnormal baseline (BL) ALT. Median BL ALT and HBV DNA were 82 U/L (IQR 56–126) and 7.4 log10 IU/mL (IQR 5.8–8.3), respectively. Compared with patients treated with TDF, ALT normalization by AASLD criteria at Week 12 (11% vs. 18%; P=0.003) and Week 48 (36% vs. 49%; P<0.001) were more common among patients treated with TAF. Similarly, ALT normalization by central laboratory criteria was greater in TAF vs. TDF-treated subjects at Week 12 (43% vs. 35%; P=0.015) and Week 48 (78% vs. 72%; P=0.012). Patients with elevated ALT at Week 48 had a higher prevalence of overweight (45% vs. 29%; P<0.001), hypertension (15% vs. 10%; P=0.007), dyslipidemia (11% vs. 6%; P=0.003), and diabetes (8% vs. 5%; P=0.062) compared with those with normal ALT. In a multivariate analysis, TAF treatment (odds ratio [OR] 0.60; 95% CI 0.44–0.82; P=0.002) and virologic suppression (OR 0.33; 0.22–0.49; P<0.001) were associated with a lower likelihood of ALT elevation at Week 48. Additional independent predictors of ALT elevation included female sex (OR 1.79; 1.29–2.47; P<0.001), higher BMI (OR 1.14; 95% CI 1.09–1.19; P<0.001), diabetes (OR 2.27; 1.11–4.63; P=0.024), cirrhosis (OR 2.64; 1.53–4.57; P<0.001), and lower BL ALT (OR 0.995; 95% CI 0.993–0.997; P<0.001). Conclusions: In patients with CHB, treatment with TAF compared with TDF is associated with a greater likelihood of ALT normalization independent of virologic suppression. Patients with metabolic risk factors are less likely to normalize ALT, which could occur due to underlying hepatic steatosis. Funding Agencies: Gilead Sciences, Inc.